An Operational Status of Micro Enterprises in Karnali Province of Nepal - Muktan, Bhim Bahadur; Gupta , Gopal Sharan (A Bi-annual South Asian Journal of Research & Innovation, 2024)
The study is based on micro-enterprises operating status in Karnali province of Nepal. Investments in global economic growth are multi-sectoral in every country in the world. Economic growth and development in various countries vary from one country to the next as the characteristics of the micro, small, medium, and large enterprises vary considerably. Micro and small enterprises (SMEs) are pivotal to addressing unemployment, driving job creation and generating income. Develps social stability, and contributing to national development. This study employed a descriptive and analytical approach, relying on secondary data sources. It has provided an overview of the micro-enterprise landscape in Karnali Province, where 157 micro-enterprises have been established over recent years. Among these, the largest share is in the milling service sector (23.57%), while the dairy sector has the smallest representation (2.55%). The study identifies a total of 30 distinct types of micro-enterprises operating within the province.